Conjugated polymer and transition metal oxide based hybrid materials : synthesis, characterization, and electrochromism - Ling, Han (2016)
Electrochromism is a phenomenon that some materials involving reversible color changes through redox reactions under electrical stimulus. This PhD work is aimed at developing hybrid materials based on conjugated polymers (CPs) and transition metal oxides (TMOs), which combine the advantages of both materials and exhibit enhanced electrochromic properties, and understanding the underlying mechanisms. Tungsten trioxide (WO3) and poly(3,4-ethylenedioxythiophene) poly(styrene sulfate) (PEDOT:PSS) or its derivatives were employed to produce hybrid EC materials and devices. Firstly, the hybrid EC materials based on WO3 nanoparticles (NPs) and PEDOT:PSS were synthesized through the layer-by-layer (LBL) assembly method. Polyethylenimine (PEI) was applied to promote the electrostatic force between the two components. Single component films, namely PEDOT:PSS and WO3-NP films, were also fabricated as reference films through the same method. The hybrid films exhibit enhanced EC properties, especially the coloration efficiency (117.7 cm2/C), compared with the reference films. The enhancement may be attributed to the efficient charge transfer process between components, since the hybrid film exhibit enhanced electrical conductivity during switching as verified by the scanning electrochemical microscopy (SECM). According to literature and SECM results, the WO3 films experience conductive-to-nonconductive transition as applied potentials go from positive to negative, while the PEDOT:PSS presents high conductivity at its oxidized state. Therefore, in the hybrid system, the synergistic interactions between components promote the enhanced charge transfer process, resulting in improved EC performance. However, the nonconductive PEI layers involved may prohibit the redox reactions and the charge transfer process in the hybrid system, which would lower the EC performance. Secondly, to further improve the EC performance, the hybrid films based on WO3 and PEDOT:PSS were synthesized by one-pot sequential electrodeposition method without any PEI component. Single component films of same thickness were also produced as reference films. Compared with the reference films, the hybrid films exhibit significantly improved EC properties, especially the optical contrast (47%) and electrochemical stability. It’s resulted from the simultaneous switching and synergistic interactions of two components. The morphology and structure of the hybrid films can be manipulated through tailoring the electrodeposition parameters to enlarge the interfacial area, leading to efficient interactions between the components. Thirdly, the charge-balancing dopant PSS involved in the aforementioned hybrid systems is an electrical insulator, which may block the charge transfer process between WO3 and PEDOT, and lower the EC performance. Poly(4-(2,3-dihydrothieno[3,4-b]-[1,4]dioxin-2-yl-methoxy)-1-butane sulfonic acid (PEDTS) is a self-doped PEDOT derivative bearing a sulfonate group in each repeat unit. It was employed to replace PEDOT:PSS in the hybrid systems. A hybrid aqueous suspension was obtained through mixing the EDTS monomers and WO3 NPs in acidic solutions, where the PEDTS were obtained through air-assisted chemical oxidation and spontaneously attached onto the WO3 NPs. The electrochromic devices (ECDs) assembled based on the hybrid films through air-brush spraying exhibit significantly improved optical contrast and electrochemical stability owing to the enhanced synergistic interactions between the two active components. In conclusion, the combination of WO3 and PEDOT:PSS or its derivatives is an effective way to improve the electrochromic properties owing to the synergistic interactions between the components. The polymers may act as buffer components for WO3, while the WO3 can prevent the over-oxidation of the polymers in the hybrid systems. And the combination of the two components also facilitates the charge transfer process in the hybrid system.